Hyperlipidemia patients with long-term statin treatment are associated with a reduced risk of progression of benign prostatic enlargement. (9th April 2021) - Shih, Hung-Jen; Tsai, Pei-Shan; Wen, Yu-Ching; Kao, Ming-Chang; Fan, Yen-Chun; Huang, Chun-Jen
Abstract: Objective: To evaluate the impacts of statin treatment on the risk of benign prostatic enlargement (BPE) progression in hyperlipidemia patients. Methods: Newly diagnosed hyperlipidemia patients ( n = 7961), identified from Taiwan's National Health Insurance Research Database, were divided into four statin cohorts (statin use >365 days, n = 1604; statin use 181–365 days, n = 813; statin use 91–180 days, n = 739; and statin use 31–90 days, n = 713) and one control cohort (cohort that used no statins, n = 4092). Study endpoint was occurrence of BPE progression (BPE diagnosis plus receiving BPE-related medications or surgery). Relative risks of BPE progression in the statin cohorts compared to the control cohort were analyzed. Results: Multivariable Cox proportional hazards regression analyses demonstrated that BPE progression risk in the cohort used statins for >365 days was significantly lower than the control cohort (adjusted hazard ratio: 0.70, 95% confidence interval: 0.58 ∼ 0.85, p < .001). However, BPE progression risks of the other three statin cohorts did not significantly differ from the control cohort. Trend analysis revealed that the effects of statin treatment on decreasing BPE progression risk were significantly related to statin treatment duration ( p = .001). Conclusions: Hyperlipidemia patients with long-term statin treatment (more than 365 days) are associated with a reduced risk of BPE progression.